System Monitoring Penyiraman Tanaman Jambu Jambu Biji Varietas Kristal (Psidium Guajava L.) Menggunakan Fuzzy Mamdani Berbasis IoT (Internet Of Things) - ari kholis fazari; Ihsan Supono; Achmad Hindasyah (Teknik Informatika Universitas Pamulang, 2022)
Media from the main source of substances in a plant is soil, soil plays an important role in the growth cycle of a plant, one of which is crystal guava plants, soil moisture affects the growth of crystal guava, because crystal guava can grow well on soil media with moisture. which is quite high, but the regulation of humidity levels in crystal guava plants is currently still not optimal, namely by watering manually, from these problems an IoT-based watering system is made using the principle of fuzzy logic. From the test, it was obtained a comparison of test results on crystal guava plants using a soil moisture meter, namely a moisture meter which has a range of 1 - 10 for dry conditions with a humidity value, 1 humidity 3, humid conditions with a humidity value, 3 Humidity 7, and wet conditions with a humidity value of 7 humidity 10 on the hygrometer display, using the Mamdani fuzzy logic method, the system is able to operate in dry conditions at the hygrometer value into humid conditions with a value of 8-10 on the hygrometer, so that the effectiveness of watering and humidity regulation can be more optimal . Keywords: Thinkspeak; IoT; Fuzzy; DHT 22; Soil Moisture Sensor, Humidty